Association of left atrial ejection fraction and cardiovascular outcomes in Asian patients with hypertrophic cardiomyopathy. (25th January 2023) - Sari, N Y; Li, T Y W; Yeo, S; Ngiam, N J H; Lee, C H; Evangelista, L K M; Lee, E C Y; Yeo, T C; Yip, J W L; Poh, K K; Kong, W K F; Lin, W Q; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): National University of Singapore Yong Loo Lin School of Medicine's Junior Academic Fellowship Scheme Background: The optimal method of risk stratification of hypertrophic cardiomyopathy (HCM) patients, especially in the Asian population, is unknown. Left atrial ejection fraction (LAEF) is an emerging risk marker for cardiovascular outcomes. This study aimed to investigate whether LAEF was associated with cardiovascular outcomes in Asian patients with HCM. Methods: This was a retrospective cohort study performed in a tertiary academic centre involving 291 consecutive patients diagnosed with HCM between 2010 and 2017. We collected the relevant clinical characteristics of these patients and retrospectively analysed the index transthoracic echocardiograms for novel left atrial indices including LAEF. We obtained the maximum (LAVmax) and minimum left atrial volumes (LAVmin) using the biplane method of disks in apical 4- and 2-chamber views. LAEF was derived by dividing the difference between LAVmax and LAVmin by LAVmax. We assessed the patients for outcomes of (1) heart failure requiring admission, and (2) a composite of adverse outcomes including all-cause mortality, ventricular tachycardia / ventricular fibrillation (VT/VF) events, appropriate device therapy if an implantable cardioverter defibrillator (ICD) was implanted, stroke and heart failure hospitalization. Results: The patients had a mean age of 59.0 ± 16.7 years-old at diagnosis and had a male preponderance (71.2%). The most common comorbidities were hypertension, diabetes mellitus and ischemic heart disease. On univariable logistic regression analysis, maximum and minimum left atrial volume index (LAVI) as well as LAEF showed a significant association with heart failure and the predefined composite outcome. On Cox regression analysis adjusting for variables of age, sex, left ventricular ejection fraction (LVEF), left ventricular maximal wall thickness >30mm, significant left ventricular outflow tract (LVOT) gradient of > 30mmHg and more than moderate mitral regurgitation, maximum and minimum LAVI as well as LAEF retained an association with heart failure admission but only minimum LAVI and LAEF were associated with the composite outcome [(OR 0.019, 95% CI 0.02-0.230, p=0.002), (OR 0.226, 95% CI 0.053-0.960, p=0.044), (OR 1.030, 95% CI 1.016-1.045, p<0.001), and (OR 1.016, 95% CI 1.005-1.026, p=0.004) respectively]. Conclusion: LAEF was an independently associated with congestive heart failure as well as a composite of adverse outcomes in Asian patients with HCM.